Identification of Film-Forming Species during SiC-CVD of CH3SiCl3/H2 by Exploiting Deep Microtrenches. (31st July 2019) - Shima, Kohei; Sato, Noboru; Funato, Yuichi; Fukushima, Yasuyuki; Momose, Takeshi; Shimogaki, Yukihiro
Abstract : The surface reaction kinetics of chemical vapor deposition (CVD) of silicon carbide (SiC) from methyltrichlorosilane (MTS; CH3 SiCl3 ) and hydrogen were studied to identify gaseous species contributing to SiC film formation. First, SiC was deposited into relatively deep microtrenches with aspect ratios of up to 64:1, and the film-thickness profiles within the deep microtrenches were analyzed to evaluate the sticking probabilities ( η ) of the film-forming species. Two film-forming species were identified with η of 10 −2 and 10 −5 at 1, 000°C. Next, their partial pressures at several positions in the reactor were estimated from their respective η and deposition rates. The low- η species was identified as MTS by comparing the partial pressure measured by quadrupole mass spectrometer with that calculated by elementary reaction simulations. Similarly, the high- η species was likely CH2 SiCl3  generated via gas-phase decomposition of MTS. Such identification is crucial to optimize the deposition conditions and also design of a reactor.